Regorafenib in the Real-Life Clinical Practice: Data from the Czech Registry - Kopeckova, Katerina; Buchler, Tomas; Bortlicek, Zbynek; Hejduk, Karel; Chloupkova, Renata; Melichar, Bohuslav; Pokorna, Petra; Tomasek, Jiri; Linke, Zdenek; Petruzelka, Lubos; Kiss, Igor; Prausova, Jana (Targeted oncology, 2017)
OBJECTIVE: To describe the use of regorafenib for the treatment of metastatic colorectal cancer (mCRC) in clinical practice in the Czech Republic, and to describe the clinical outcomes of patients in terms of safety and survival. PATIENTS AND METHODS: The data of patients treated with regorafenib were extracted from the national CORECT registry. The CORECT registry is a non-interventional post-marketing database, gathering information about patients with CRC and treated with targeted agents. Twenty oncology centres in the Czech Republic contributed to this registry. Collected data included patients' characteristics, disease history, cancer treatments, response to treatments and safety. RESULTS: A total of 148 patients treated with regorafenib in clinical practice were analysed. At regorafenib initiation, almost all patients were fully active or slightly restricted in physical activity. Regorafenib was not administered as first-line treatment in any patient. Median progression-free survival was 3.5 months and median overall survival was 9.3 months. One-year survival rate was 44.6 %. Four partial responses were observed and 51 stable diseases. Progression was observed in 66 patients (44.6 %). The main reported adverse events were skin toxicity (5.4 %) and fatigue (2.0 %). CONCLUSIONS: Regorafenib is a well-established treatment for pretreated patients with mCRC, however real-life data are scarce. Our results demonstrated slightly better efficacy of regorafenib and better safety profile in patients with mCRC compared to the randomised trials.
Keywords: Registries; Humans; lidé středního věku; registrace; Antineoplastic Agents; lidé; Pyridines; Phenylurea Compounds; Neoplasm Metastasis; metastázy nádorů; kolorektální nádory; Male; Middle Aged; Czech Republic; pyridiny; protinádorové látky; fenylmočovinové sloučeniny; Česká republika; mužské pohlaví; Colorectal Neoplasms